The role of peer relationships in adolescents’ psychological well-being - Liu Yawen (SHS Web of Conferences, 2023)
As a crucial period of development, adolescence builds the foundation of how a person would become. Peer relationship is considered to be a vital part of adolescents’ interpersonal relationships, which naturally contributes to shaping a psychological well-being for them. This review primarily pays attention to the role played by peer relationship. Peer relationship serves as a shaping factor of adolescents’ behaviors as adolescents tend to mirror how their peers behave. Meanwhile, peer relationship can work with adult support, such as teacher relationships and parental relationships, and thus benefit adolescents’ psychological well-being in a further way. Moreover, gender difference should not be neglected when discussing the role played by peer relationship in the psychological well-being of adolescents. In respect of the influence of stressful life events, girls’ peer relationship quality is more affected than boys’ is. Concerns about this review may be that not enough studies on the field of adolescents’ psychological well-being are reviewed and different results may thus not be considered. For future research, the role of peer relationship in other age groups’ psychological well-being (middle-aged and elderly) can be studied.